Day-of-the-week effect on the Tunisian stock market return and volatility - Abdelkader Derbali; Slaheddine Hallara (Cogent Business & Management, 2016)
In this paper, we examine empirically the day-of-the-week effect on the Tunisian stock exchange index (TUNINDEX) return and volatility. We use three multivariate general autoregressive conditional heteroscedasticity models (GARCH (1,1), EGARCH (1,1), and TGARCH (1,1)) to examine the presence of daily anomalies in the TUNINDEX returns and volatilities during the period from 31 December 1997 to 07 April 2014. The empirical results of GARCH (1,1), EGARCH (1,1), and TGARCH (1,1) model indicate the existence of a significance and positive effect for Thursdays and for the return at (t - 1) on the return and volatility of TUNINDEX in a threshold of 1%. Additionally, we find the presence of a significance and negative effect for Tuesday on the TUNINDEX return and volatility. Also, we can show the persistence of volatility in the case of Tunisian stock market index.
Keywords: 650